Distribution and functional identification of complex class 1 integrons - Quiroga, María Paula (2013)
The emergence of extended-spectrum b-lactamases and plasmid-mediated resistance to quinolones has been previously found to be associated with the dissemination of complex class 1 integrons in Argentina. In this study, we analyzed their distribution through time and evaluated the functionality of the Orf513 pro- tein, which is the putative recombinase of the ISCR1 mobile element. We investigated the presence of the orf513, blaCTX-M-2, dfrA3b, qnrB10 and blaDHA-1 genes by PCR and DNA sequencing as well as their linkage to class 1 integrons in 451 non-epidemiologically related nosocomial strains resistant to at least one expanded-spectrum cephalosporin and to one aminoglycoside, isolated between 1989 and 2010 from 7 hospitals from Buenos Aires City. The epidemiology of complex class 1 integrons was found to be notably different among fermenting (94/171) and non-fermenting clinical bacilli isolates (1/280). The ISCR1::qnrB10 positive isolates were found since 1993, confirming its presence in clinical isolates more than a decade before its first description. As expected, In35::ISCR1::blaCTX-M-2 was the most common complex class 1 integron among Enterobacteriaceae isolates, particularly in Proteus mirabilis. Experimental analysis corroborated the activity of the Orf513 protein, which was found to bind specific DNA sequences containing the previously suggested oriIS region. These findings showed the high dispersion and maintenance of com- plex class 1 integrons across time in our nosocomial isolates. The contribution of the ISCR1 mobile element to multidrug resistant phenotypes is significant due to its sustained association to class 1 integrons.